A COMPARATIVE STUDY USING FOUR PR MODELS — THE PRESS AGENTRY, PUBLIC INFORMATION, TWO-WAY ASYMMETRICAL AND TWO SYMMETRICAL ON MALAYSIA GOVERNMENT - Mustafa, Muhamad Zaki; Sofian, Muhammad Raqib Mohd; Sabri , Safiyyah Ahmad; Ariffin , Mohd Yahya Mohd; Kasmani , Mohd Faizal (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the dynamics of Facebook engagement by a Malaysian ministry, emphasizing its communication objectives, strategies, and outcomes. In light of the increasing role of social media in public administration, the research seeks to uncover how Facebook is utilized for public communication and information dissemination. Method: A quantitative content analysis was conducted on all Facebook posts published between January and June 2023. The analysis examined post characteristics and audience engagement metrics, including likes, shares, and comments. Results: The findings reveal that posts featuring public service announcements and interactive content generated the highest levels of engagement. The study also identifies that strategic content planning and audience-targeted messaging are critical in enhancing public interaction. Novelty: This research contributes to the limited literature on social media engagement strategies within governmental institutions in Malaysia, offering empirical insights into optimizing Facebook as a tool for fostering public participation and transparency.